TEACHERS STRATEGIES IN TEACHING READING COMPREHENSION - Novi Yanti; Clarry Sada; Eusabinus Bunau (Universitas Tanjungpura, 2022)
AbstractThe purpose of this research was to discover what strategies used by the English teacher and what strategies frequently used by the teacher in teaching reading comprehension Immanuel 2 Sungai Raya, Academic Year 2019/2020 by using questionnaire and depth interview. The subject of this research was an English teacher who has been teaching English since 2002 at the school. Besides being an English teacher, he is also a vice headmaster at the school. The type of this research was case study. The data were collected by using questionnaire and interview. The questionnaire was distributed to the students as the supported participants by google form meanwhile the interview had been done by phone. From the result of questionnaire and interview that was analyzed, it showed that the strategies used by the teacher were 71% scaffolding, 78.8% think aloud and 79.4% QAR strategy. From this result, it is noticeable that the teacher cannot rely on only single teaching strategy. As a conclusion, the teacher frequently used QAR strategy.Keywords: reading comprehension, teaching reading comprehension.